2007
DOI: 10.1002/clc.20066
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Nanoparticle Paclitaxel (nab‐Paclitaxel) for In‐stent Restenosis I (SNAPIST‐I): A First‐in‐Human Safety and Dose‐finding Study

Abstract: SummaryBackground: Paclitaxel-eluting stents inhibit restenosis; however, this technology has drawbacks (e.g., stent thrombosis, requirement for long-term antiplatelet therapy, and cost-particularly for patients with multivessel disease). Systemic treatment with a novel 130-nm, albumin-bound particle form of paclitaxel (nabpaclitaxel) has been shown to reduce restenosis in animals.Hypothesis: This study was designed to establish the safety and optimal dose of systemic nab-paclitaxel for reducing in-stent reste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 15 publications
0
46
0
1
Order By: Relevance
“…Margolis et al 14 reported no relevant side effects ≤50 mg/ patient. A study reporting hematologic analyses after the use of multiple paclitaxel-coated balloon catheters in femoro-popliteal vessels up to a dose of ≈25 mg/patient did neither indicate paclitaxel plasma levels coming close to those known to cause systemic effects nor changes in cell counts which would indicate systemic toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…Margolis et al 14 reported no relevant side effects ≤50 mg/ patient. A study reporting hematologic analyses after the use of multiple paclitaxel-coated balloon catheters in femoro-popliteal vessels up to a dose of ≈25 mg/patient did neither indicate paclitaxel plasma levels coming close to those known to cause systemic effects nor changes in cell counts which would indicate systemic toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…The risk of systemic effects due to paclitaxel was addressed in a clinical study on the pharmacokinetics of paclitaxel released from coated balloons in peripheral arteries [79]. Based on this study and the experience with intravenous administration of paclitaxel [83,84], up to 7 balloon catheters 6.0 × 120 mm may be used in adult patients during one intervention without reaching the dose known to cause systemic adverse effects.…”
Section: Peripheral Trialsmentioning
confidence: 99%
“…The phase 1 study has been conducted showing 10-30 mg/m 2 doses of the drug are safe for humans 132 . The phase II study is ongoing.…”
Section: Paclitaxel and Its Analoguesmentioning
confidence: 99%